Adoption of electric vehicles in commercial fleets: Why do car pool managers campaign for BEV procurement?. (October 2018) - Globisch, Joachim; Dütschke, Elisabeth; Wietschel, Martin
Highlights: Technophile car pool managers are more likely to campaign for BEV adoption. Perceived environmental benefits of BEVs foster individual adoption initiatives. Expected employee motivation by BEVs fosters individual adoption initiatives. Fear of mobility constraints hinders initiatives for (additional) BEV adoption. Fear of reduced reliability hinders initiatives for (initial) BEV adoption. Abstract: We use regression analysis to study what motivates car pool managers to campaign for BEV procurement using primary data from 229 car pool managers including adopters and non-adopters of EVs. Key findings are that a personal interest in EVs due to technophilia increases the intention to start procurement initiatives for BEVs. These findings underpin the fact that the attitudes of single individuals can influence internal organizational decision processes and therefore play an important role in explaining BEV adoption in commercial fleets. Other factors that foster initiatives for BEV procurement are organizational innovativeness, and the expectation of environmental benefits and positive effects on employee motivation. The fear of mobility constraints and doubts about the reliability of BEVs counteract the intention to campaign for their procurement.